2018
DOI: 10.21273/hortsci12391-17
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Using Canopy and Leaf Reflectance for Estimating Nitrogen Status in Red-blush Pears

Abstract: Abstract. Reflectance measurements at leaf and canopy scales were made in a red-blush pear (Pyrus communis) orchard for two growing seasons. Canopy reflectance measurements were obtained using a multispectral camera flown on board an unmanned aerial vehicle (UAV), and leaf reflectance measurements were undertaken in a laboratory using a portable spectrometer. These measurements were used to compute reflectance indices as surrogates for direct leaf nitrogen (N) concentration measurements. The indices were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 9 publications
(12 reference statements)
1
15
0
2
Order By: Relevance
“…Geipel et al [19] found that the normalized difference vegetation index (NDVI) and red-edge inflection point (REIP) from UAV multispectral remote sensing explained 72-85% of winter wheat aboveground biomass (AGB) and 58-89% of plant N concentration (PNC). Perry et al [20] reported a good performance (R 2 = 0.67) for estimating leaf N concentration of red-blush pears (Pyrus communis L.) using multispectral camera form UAV with a new red-edge index. Zheng et al [21] reported that some blue band-based VIs performed consistently well for estimating rice (Oryza sativa L.) PNC (R 2 = 0.39-0.68) across growth stages using UAV-based multispectral imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Geipel et al [19] found that the normalized difference vegetation index (NDVI) and red-edge inflection point (REIP) from UAV multispectral remote sensing explained 72-85% of winter wheat aboveground biomass (AGB) and 58-89% of plant N concentration (PNC). Perry et al [20] reported a good performance (R 2 = 0.67) for estimating leaf N concentration of red-blush pears (Pyrus communis L.) using multispectral camera form UAV with a new red-edge index. Zheng et al [21] reported that some blue band-based VIs performed consistently well for estimating rice (Oryza sativa L.) PNC (R 2 = 0.39-0.68) across growth stages using UAV-based multispectral imagery.…”
Section: Introductionmentioning
confidence: 99%
“…The model that combined supported vector machine (SVM) and least square methods could estimate the starch content of mature leaves with R = 0.6822. In a red-blush pear orchard, Perry et al used a six-band (at 550, 660, 710, 720, 730, 810 nm, and all bands were 10 nm wide) multispectral camera to collect images of the canopy with UAV [83]. They provided a new index, the Modified Canopy Chlorophyll Content Index (M3CI_710 nm), utilized for the assessment of canopy nitrogen.…”
Section: Detection Of Pigment and Nutrient Contentsmentioning
confidence: 99%
“…Two reflectance measurements were demonstrated, one is canopyscale reflectance measurement with the contribution of UAVs, the other is leaf-scale measurement in laboratory level. For the canopy-scale measurement, a result for root mean square error (RMSE) value is 0.24%N, resulted in a new index, modified canopy chlorophyII Content Index, which provided a support for spatial variation of leaf N concentration (Perry et al 2018). In a thermal image, if different images indicate different temperature values for a same location in the terrain, thermal drift happens.…”
Section: Health Statusmentioning
confidence: 99%
“…Image processing and analysis were employed for the canopy reflectance measurement, specifically, for the nitrogen status estimation in a pear orchard (Perry et al 2018). For thermal drift correction, six mathematical correction models were build up, and a line method defines the relationship between sensor temperature and absolute temperature was applied (Mesas-Carrascosa et al 2018).…”
Section: Health Statusmentioning
confidence: 99%